Sex Differences Among Opioid-Abusing Patients With Chronic Pain in a Clinical Trial. Issue 1 (January 2015) - Manubay, Jeanne; Davidson, Jesse; Vosburg, Suzanne; Jones, Jermaine; Comer, Sandra; Sullivan, Maria
<x xml:space="preserve">Abstract</x> Background: The characteristics of patients with co-occurring chronic pain and prescription opioid abuse have not been well described, and even less is known about differences between men and women in this population. Objectives: This study evaluated sex differences in the demographic, diagnostic, and behavioral attributes of patients with chronic pain and opioid abuse. Methods: Data were collected via self-report and semistructured clinical interviews from 162 patients (120 men and 42 women) who screened for a study investigating the abuse liability of prescription opioids. Results: There were no differences between men and women in age, race, education, marital status, or employment status. Participants had used prescription opioids for 5.4 ± 6.7 years. The majority of participants (60%) had low back pain in addition to opioid dependence as defined by the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition. More women reported more arthritic pain than men, but otherwise there were no differences in types of pain. Pain exerted a greater effect in women on mood, walking ability, and social relations. Men reported more of certain aberrant behaviors, including abuse of alcohol or illicit drugs, unauthorized dose increases, contact with street culture, and being arrested by police. Women were more depressed than men. Conclusions: The demographic profile of opioid-abusing patients with chronic pain presenting for treatment in a clinical trial was similar between sexes; however, some important differences were observed. Women reported more psychiatric comorbidity and endorsed greater pain-related physical and social impairment. Men reported more aberrant behaviors. These differences suggest that men with chronic pain and opioid abuse/dependence may benefit by closer monitoring of aberrant behaviors whereas women may benefit from closer attention paid to physical and psychological effects of pain.